THE EFFECTIVENESS OF USING PHONICS INSTRUCTION AND STORYBOOKS IN ENGLISH READING CLASSES TO IMPROVE STUDENT PARTICIPATION - Wahyuni, Naning Tri (Jurnal Penelitian Humaniora, 2016)
The purpose of this study is to examine the effectiveness of instructional methods based on phonics instruction in reading classes to improve students participation therefore they can develop to their maximum potential. Using qualitative tools ofobservation, documentation and interview, this research was focusing the inquiry on investigating studentsâ reception to the phonics instruction model, observing their participation in the classroom activities, also investigating instructional methodswhich attract students to more actively contribute in learning activities. The finding shows that the reception of students to the model was good and they showed much eagerness in following the program. Further investigation revealed that studentskeen to participate more in the classroom activities especially in certain activities with the use of sound sheets, sound book, flash card sheets, word box sheets, songs, games and storybooks. However, there were two challenges identified during 16weeks running the study; the lack of teachersâ skill in delivering this method efficiently also the limited collection of English story books in school. Hence, to improve the effectiveness of the use of phonics instruction in reading classroom, firstly, training for teachers would be needed to deliver the method effectively, secondly, considering the fact that school still have limited collection of English story books or any English books, the collaboration with government agencies or other promising bodies could be done to help in providing more collection of storybooks in school.